Proposal of a new approach for BER evaluation of multirate, multiservice OCDMA systems - Raddo, Thiago Roberto (2012)
The continuous evolution of the optical communication technology in the last few years has allowed the growing users demand for higher bandwidth to be satisfactorily attended. This new demand is mainly attributed to the growing popularity of bandwidth-intensive networking applications, such as Internet protocol television (IPTV), high-definition television (HDTV), e-learning, e-health, super high-definition (SHD) class digital movies, and e-culture based on 3-D full-HD video. These applications will eventually require differentiated service types and diversified data rates. As a result, capability of supporting differentiated-quality of service (QoS) and multirate transmission are becoming a challenge for future optical networks. Among many multiplexing techniques, optical code-division multiple-access (OCDMA) constitutes a potential candidate for next generation optical networks, particularly due to features like asynchronous operation, simplified network control, easy addition of new users, and possibility of differentiated-QoS at the physical layer. The performance of this access technique is mainly limited by multiple-access interference (MAI). Although in multirate, multiservice OCDMA systems MAI is considered to be binomially distributed, others probability distributions for the MAI analyzes and consequently the bit error rate (BER) have been used as an approximation. In this context, this dissertation proposes a new formalism to evaluate the BER performance of 1-D and 2-D multirate, multiservice OCDMA systems considering MAI as binomially distributed, resulting in a more accurate BER expression. Also, the proposed approach does not require knowledge a priori of the generated code sequences themselves, which means that the system performance analysis is achieved more easily using only the code parameters. Furthermore, a multirate OCDMA system employing 1-D optical orthogonal code (OOC) and 2-D optical fast frequency hopping (OFFH) codes is also investigated. A performance comparison in terms of BER for the OOC-based system assuming both Poisson and binomial distribution for the MAI is investigated. A further comparison of an OFFH-based multirate system assuming both gaussian and binomial distribution for the MAI is also analyzed. It is shown that BER performance in multirate scenarios can be overestimated or underestimated by many orders of magnitude depending on the assumed distribution for the MAI and on the number of simultaneous users. Moreover, it is presented for the first time a hybrid OCDM/WDM optical packet switch capable of supporting multirate and differentiated-QoS transmission. The architecture of the proposed multirate switch and its performance in terms of packet loss probability are also presented. Finally, it is shown that using a gaussian or Poisson distribution for the MAI might not be appropriate for a reliable BER estimate, since they are not acceptable approximations to assess the performance of multirate, multiservice systems with good accuracy.